Dielectronic Recombination in He-like, Li-like and Be-like Iodine and KLM Resonances - YUMAK YAHŞİ, AYŞE; BLEDA, ERDİ ATA; YAVUZ, İLHAN; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2012)
DR rate coefficients for He-like, Li-like and Be-like Iodine ions and KLM resonances are calculated using MCBP approximation.